KEYAKINAN AGAMA DAN GANGGUAN KESURUPAN - ., Siswanto; ., Subandi; Paramastri, Ira (Universitas Muhammadiyah Jember, 2020)
Religious beliefs with possession disorders have not been mentioned much in the scientific literature. This study aims to explore religious beliefs with possession disorders and how to recover. Anthropological literature examines more possessions in terms of culture. On the contrary in the clinical field, it is difficult to find literature that addresses both of these variables. The method used is a case study with semi-structured interviews for data collection. Criteria for participants are having experienced a possession disorder by PPDGJ III at least twice. Six participants met the criteria, all women. Research indicates a link between religious beliefs and possession disorders, both related to their emergence to their recovery efforts. Possession disorder occurs when the belief that there is a spirit is accompanied by the fear that cannot be controlled by the individual concerned. Prayers, spells, songs, and other are usually used in the recovery process. Emotional factors accompanying religious beliefs need to be considered in the occurrence of possession disorders.